A Review of Research Studies for two Alternative Models in Physical Education: Sport Education and Teaching Games for Understanding - Lefteratos Χρυσόστομος; Tsangaridou Νίκη (Inquiries in Physical Education and Sport, 2010)
This article presents and reviews two teaching models, the Teaching Games for Understanding (TGfU) and the Sport Education (SE). Both models offer instructional ideas in an innovative way and give several opportunities to all students to develop themselves. The potential and prospects that open up with the implementation of these models are based on international bibliography. In addition, representative research studies from 1995 till today are reviewed and analyzed. These studies are presented in tables with an emphasis in the purpose of the study, the participants, the settings, the way of collecting data and the main results. Finally, the findings are grouped in the six categories: (a) Development of Motor Skills, (b) Enhancement Tactical Knowledge, (c) Decision-Making, (d) Development of the Social and Personal Responsibility, (e) Students’ Attitudes and (f) Student Enrollment. The results suggested that both models provide alternative ways of how to provide more quality teaching experiences in physical education settings.